An exact implementation of the Nash bargaining solution in dominant strategies - Walter Trockel (Institute for Advanced Studies (IHS), 1996)
For any abstract bargaining problem a non-cooperative one stage strategic game is constructed whose unique dominant strategies Nash equilibrium implements the Nash solution of the bargaining problem.
Keywords: C78; 330; Nash programm; implementation; Nash bargaining solution